2016
DOI: 10.1038/nrurol.2016.70
|View full text |Cite
|
Sign up to set email alerts
|

Advances in laparoscopic surgery in urology

Abstract: In the past 10 years, laparoscopy has been challenged by robotic surgery; nevertheless, laparoscopic techniques are subject to continuous change. Ultrahigh definition is the next development in video technology, it delivers fourfold more detail than full high definition resulting in improved fine detail, increased texture, and an almost photographic emulsion of smoothness of the image. New 4K ultrahigh-definition technology might remove the current need for the use of polarized glasses. New devices for laparos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
11

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 77 publications
0
33
0
11
Order By: Relevance
“…A substantial disadvantage of pure laparoscopy is the reduced range of motion due to a fixed trocar position, which determines the angle of the laparoscopic instrument in the working field 13 . Such disadvantage in terms of ergonomics is critical during difficult processes, including reconstructing parts.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial disadvantage of pure laparoscopy is the reduced range of motion due to a fixed trocar position, which determines the angle of the laparoscopic instrument in the working field 13 . Such disadvantage in terms of ergonomics is critical during difficult processes, including reconstructing parts.…”
Section: Discussionmentioning
confidence: 99%
“…Die Einführung der digitalen High-Definition (HD)-Videotechnologie kann sicherlich als Quantensprung für die gesamte Endoskopie gesehen werden mit signifikant verbesserter Auflösung, Tiefenschärfe und Helligkeit. Damit hat sich die Laparoskopie dem Dogma der schlechteren Bildqualität als beim offenen Operieren entledigt: Im Gegenteil, durch die Nähe des Laparoskops zum Objekt besteht eine deutlich bessere optische Darstellung der anatomischen Strukturen [1]. Außerdem steht wie in der Unterhaltungsindustrie die 4K-Ultra-HD-Television vor dem breiten klinischen Einsatz mit weiterer Optimierung der Bildqualität mit 8 Millionen Pixel im Vergleich zu 2 Millionen Pixel der HD-Videotechnologie (▶ Tab.…”
Section: Videotechnologieunclassified
“…Inzwischen gibt es auch unterschiedliche mechanische und elektro-mechanische Lösungsansätze für die klassische Laparoskopie, wie das Radius-System und Cambridge Endo bzw. Kymerax, Dexterité und Human Extension [1]. Die rein mechanischen Geräte nützen die Beweglichkeit des Handgelenks zur Umsetzung des Bewegungen der Instrumentenspitze (▶ Abb.…”
Section: Instrumente Mit 7 Freiheitsgradenunclassified
“…This technique provide a complete video and image of operative area. 10 Previous studies on this topic also shown results in favour of endoscopic ligation in terms of minimum complications and postoperative recovery till one year of procedure, and it is documented that endoscopic haemorriodectomy should be preferred over conventional haemorriodectomy in the treatment of internal bleeding hemorrhoids.…”
Section: Introductionmentioning
confidence: 98%